How an Abortion Ban Would Impact Wrongful Birth Claims in the United States (TEST Trento Student Law Review, 2020)
Recently, several USA states have enacted abortion laws that restrict women's reproductive freedom. These laws are generally being challenged and the United States Supreme Court is expected to hear cases about them in order to affirm whether they are constitutional or not. If the Supreme Court decided that these laws are constitutional and allowed states to establish strict regulations on abortion, then it would create issues concerning wrongful birth claims across the United States. In this context, also assuming hypothetical enaction of state-by-state or nationwide abortion bans, which would be the possible effects and the proposals to alleviate potential issues that these restrictions would arise?
Keywords: Abortion ban; Wrongful birth claim; Abortion right; Conscience exemptions; Medical liability